1963
DOI: 10.1021/jf60126a004
|View full text |Cite
|
Sign up to set email alerts
|

Chelation in Nutrition, Soil Microorganisms and Soil Chelation. The Pedogenic Action of Lichens and Lichen Acids

Abstract: The role of chelation within the soil itself is discussed. The usefulness of lichens for studying early stages of pedogenesis was investigated. Interactions between soil-, rock-, and bark-inhabiting lichens with powdered granite, muscovite, and greensand marl were determined by changes in light transmission of the aqueous supernatant solutions. Physodic Table I. Species, Acid Content, and Source of Lichens lichens Baeomyces roseus Cladonia furcata C. sylvatica Peltigera aphthosa Caloplaca elegans Parmelia cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

1972
1972
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 8 publications
0
37
0
3
Order By: Relevance
“…On the one hand, their limited solubility in water could suggest they do not play an important role in mineral weathering, but, on the other, Ascaso et al (1976) reported that P. conspersa thalli demonstrate the ability to extract cations (including Ca 2+) when suspended in water minerals and rocks. Also, relatively low pH = 4.5 measured in P. conspersa water suspension and pH = 5.3 measured in P. conspersa-mica water suspension (Schatz 1963) indicate that chemical weathering processes may occur in granitic rock components. Wierzchos and Ascaso (1996) recently demonstrated that the lichen-rock interface could be an important location of chemical changes of biotite.…”
Section: Semmentioning
confidence: 94%
“…On the one hand, their limited solubility in water could suggest they do not play an important role in mineral weathering, but, on the other, Ascaso et al (1976) reported that P. conspersa thalli demonstrate the ability to extract cations (including Ca 2+) when suspended in water minerals and rocks. Also, relatively low pH = 4.5 measured in P. conspersa water suspension and pH = 5.3 measured in P. conspersa-mica water suspension (Schatz 1963) indicate that chemical weathering processes may occur in granitic rock components. Wierzchos and Ascaso (1996) recently demonstrated that the lichen-rock interface could be an important location of chemical changes of biotite.…”
Section: Semmentioning
confidence: 94%
“…Se han estudiado, por ejemplo, los mecanismos de interacción entre los líquenes y los materiales de construcción [7,8], el efecto de los líquenes en diferentes tipos de tejas [9], o la relación entre la degradación de los materiales debida a la formación de compuestos a partir de sustancias producidas por los líquenes y cómo afecta esto al deterioro de los monumentos [10][11][12]. Pero no se ha realizado un estudio en el que se establezca una relación entre las características de los materiales cerámicos y la colonización biológica que permita el diseño de productos resistentes a la biocolonización.…”
Section: Ensayos Realizadosunclassified
“…There will also be significant geological impacts as root exudates will alter the chemical composition of the soil, for example increasing the concentration of CO 2 which would increase the chemical weathering of rocks and so increase rates of chemical weathering (Berner, 1997). Also of relevance is the production of acids by lichens in order to chelate minerals that can significantly alter the flux of elements from rocks into the biosphere (Schatz, 1963).…”
Section: Biological Processesmentioning
confidence: 99%